Study of the interaction between nanovesicles derived from bacteria and different pathogenic bacteria - Low, Perlie Li Hui (Nanyang Technological University, 2022)
Streptococcus pneumoniae, Staphylococcus aureus and Klebsiella pneumoniae are the three major pathogens that cause multiple severe diseases including bacterial coinfection and superinfection in respiratory pandemics. Unfortunately, conventional treatments against these bacterial infections such as antibiotics were futile as the bacteria continue to develop resistance to them. Hence, many research studies have tried to create effective vaccines. However, Staphylococcus aureus and Klebsiella pneumoniae do not have any viable vaccine to date while Streptococcus pneumoniae vaccines have limited serotype coverage. Therefore, while vaccine development is still in progress, it is also an opportunity to create novel drug delivery to address the limitation of vaccines. Extracellular vesicles (EVs) have been identified as both potential drug delivery systems and components for vaccine development. However, EV production is time-consuming and costly. Hence, in this project, Bacterial Derived Nanovesicles (BDNs), which are mimetics of extracellular vesicles, are produced as cost-efficient and scalable alternatives. In addition, the project also explores the interaction between the three aforementioned pathogens and the BDNs derived from them. The project findings have shown interaction between the three pathogens and BDNs derived from them.